Ocular Manifestations - Olabisi Olayemi Yeye-Agba; Ejike J. Egbu; Ugochukwu Anthony Eze (Clinical Manifestations of Covid-19: A Multi-Disciplinary Approach, 2024)
COVID-19 infection affects the eyes in a variety of ways. Ocular manifestations have been reported in some individuals, especially health workers. With the infection spreading to every country in the world, this pandemic has far-reaching consequences and implications on the economy of many nations and the mental health of people. The mechanism of infection by the SARS Cov-2 virus has been attributed to its affinity to angiotensin-converting enzyme 2. Reports suggest that this enzyme is expressed in the conjunctival epithelium, cornea, and retina. The ocular involvement in COVID-19 infection therefore involves structures in the eye that have angiotensin-converting enzyme 2 such as the optic nerve and nerves controlling ocular motility. The involvement of ocular adnexal tissues is sparks interest in research.